Ancient barley landraces adapted to marginal soils demonstrate exceptional tolerance to manganese limitation. (15th December 2018) - Schmidt, Sidsel Birkelund; George, Timothy S; Brown, Lawrie K; Booth, Allan; Wishart, John; Hedley, Pete E; Martin, Peter; Russell, Joanne; Husted, Søren
Abstract: Background and Aims: Micronutrient deficiency in cereals is a problem of global significance, severely reducing grain yield and quality in marginal soils. Ancient landraces represent, through hundreds of years of local adaptation to adverse soil conditions, a unique reservoir of genes and unexplored traits for enhancing yield and abiotic stress tolerance. Here we explored and compared the genetic variation in a population of Northern European barley landraces and modern elite varieties, and their tolerance to manganese (Mn) limitation. Methods: A total of 135 barley accessions were genotyped and the genetic diversity was explored using Neighbor–Joining clustering. Based on this analysis, a sub-population of genetically diverse landraces and modern elite control lines were evaluated phenotypically for their ability to cope with Mn-deficient conditions, across three different environments increasing in complexity from hydroponics through pot experiments to regional field trials. Key Results: Genetically a group of Scottish barley landraces (Bere barley) were found to cluster according to their island of origin, and accessions adapted to distinct biogeographical zones with reduced soil fertility had particularly larger Mn, but also zinc (Zn) and copper (Cu) concentrations in the shoot. Strikingly, when grown in an alkaline sandy soil in the field, the locally adapted landraces demonstrated an exceptional ability to acquire and translocate Mn to developing leaves, maintain photosynthesis and generate robust grain yields, whereas modern elite varieties totally failed to complete their life cycle. Conclusions: Our results highlight the importance of gene pools of local adaptation and the value of ancient landrace material to identify and characterize genes that control nutrient use efficiency traits in adverse environments to raise future crop production and improve agricultural sustainability in marginal soils. We propose and discuss a model summarizing the physiological mechanisms involved in the complex trait of tolerance to Mn limitation.